2011
DOI: 10.1189/jlb.1209813
|View full text |Cite
|
Sign up to set email alerts
|

Myelin ingestion alters macrophage antigen-presenting function in vitro and in vivo

Abstract: During MS, phagocytosing myelin-containing macrophages arise and lie in close proximity to T cells. To date, it has not been addressed whether these myelin-laden macrophages have the capacity to present antigens to T cells and whether this contributes to inflammation in disease. We demonstrate that in vitro-generated human and mouse myelin-laden macrophages expressed MHC class I and II and costimulatory molecules and are thus well equipped for antigen presentation. Human myelin-laden macrophages exhibited norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Previous studies have referred to myelin-containing myeloid cells as foamy macrophages. Ingestion of myelin by MDMs in vitro induces an anti-inflammatory cytokine response, a phenotype also observed in human MS lesions (4,5). Previously, we and others have observed that human adult brain-derived microglia in vitro display an increased ability to phagocytose myelin as compared with MDMs (6,7).…”
mentioning
confidence: 86%
“…Previous studies have referred to myelin-containing myeloid cells as foamy macrophages. Ingestion of myelin by MDMs in vitro induces an anti-inflammatory cytokine response, a phenotype also observed in human MS lesions (4,5). Previously, we and others have observed that human adult brain-derived microglia in vitro display an increased ability to phagocytose myelin as compared with MDMs (6,7).…”
mentioning
confidence: 86%
“…These leukocytes enter the white matter by crossing the blood-brain barrier (BBB) in areas of inflammation called the perivascular cuffs (1)(2)(3), as well as through the CNS-meningeal barrier (4,5). The accumulation and activation of leukocytes in areas of infiltration initiates a cascade of events leading to the loss of BBB integrity, which further aids the transmigration of leukocytes into the brain parenchyma (3,6,7). Recent studies highlight the existence of a metabolic switch within leukocytes that intricately regulates their activation states by changing their metabolic profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages have a bimodal action in autoimmune-mediated CNS diseases; while demyelinating incidents of the CNS drive macrophages and microglia activation thus contributing to the disease pathogenesis [6, 64, 65], macrophage clearance of myelin debris facilitates remyelination and reshapes their morphology towards acquisition of an anti-inflammatory and neuroprotective phenotype [30, 6668]. Therefore, it is of high importance to elucidate how MAPC modulate the features of myeloid cell types since intravenously transplanted cells are likely to be localized in close proximity with myeloid cells in the CNS and periphery [37, 61, 69].…”
Section: Discussionmentioning
confidence: 99%